2019
DOI: 10.1039/c9cc00716d
|View full text |Cite
|
Sign up to set email alerts
|

A chemopalette strategy for white light by modulating monomeric and excimeric phosphorescence of a simple Cu(i) cyclic trinuclear unit

Abstract: Cu3(4-chloropyrazolate)3 is presented herein to exhibit unprecedented room-temperature white phosphorescence by modulating monomeric blue and excimeric yellow phosphorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…The radiative constant value is comparable to previously reported ones for copper(I) pyrazolates. 36…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The radiative constant value is comparable to previously reported ones for copper(I) pyrazolates. 36…”
Section: Papermentioning
confidence: 99%
“…Copper(I) CTCs show phosphorescence due to emission from a metal-centered triplet state ( 3 MM) of an excimer, 31,32 and only very recently has it been reported that very high quantum yields, i.e., over 75%, are affordable in the crystal state at room temperature. [33][34][35][36] Although the planar structure of the metallacycle could facilitate the formation of columnar liquid crystal phases, liquid crystalline behaviour was not observed for copper(I) CTCs even on using the same ligands as those used for liquid crystalline silver(I) and gold(I) CTCs. 34 For example, silver(I) and gold(I) complexes with the 4-hexyl-3,5-dimethylpyrazolate ligand are liquid crystalline, but the copper(I) complex has a lower melting point and exhibits direct transition to the isotropic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…As far as trimers are concerned, the two main classes are isolated trimers and double trimers and we proposed to denote the latter as "3 + 3". The simplest derivatives of isolated trimers include CODBAB (4-Cl-pyrazolate) [40], VIJMUW (3,5-diMe-pyrazolate) [41], BELTOC (3,5-di-i-Pr-pyrazolate) [42] and XELXAN (3,5-di-CF3-pyrazolate) [43].…”
Section: Analysis Of the Reported Csd Structures (Hits) And Their Refmentioning
confidence: 99%
“…Simple examples of "3 + 3" double trimers ( Figure 4) are IDUYOW (3-Ph-pyrazolate) [44], TANRUW (3-CF3-pyrazolate) [32] and GITJIC (3,5-diMe-4-NO2-pyrazolate) [30] with near one bond between the triangles formed by Cu atoms and XOGJOU (4-NO2-pyrazolate) [45] with near three As far as trimers are concerned, the two main classes are isolated trimers and double trimers and we proposed to denote the latter as "3 + 3". The simplest derivatives of isolated trimers include CODBAB (4-Cl-pyrazolate) [40], VIJMUW (3,5-diMe-pyrazolate) [41], BELTOC (3,5-di-i-Pr-pyrazolate) [42] and XELXAN (3,5-di-CF 3 -pyrazolate) [43].…”
Section: Analysis Of the Reported Csd Structures (Hits) And Their Refmentioning
confidence: 99%
“…In fact, the observation of luminescence is quite typical for multinuclear coinage metal d 10 complexes with M3 units. [394][395][396][397][398][399][400][401][402][403][404][405][406][407][408][409] Figure 6.17: Luminescence properties of 9 H in MeCN at room temperature under inert conditions. Left: Emission spectra of 9 H (0.125 mM, solid green) and [Cp2Co](PF6) (0.884 mM, solid black) upon excitation at 342 nm normalized to Imax, as well as ∆(I/Imax) of 9 H (dotted green) with respect to the spectrum of [Cp2Co](PF6).…”
mentioning
confidence: 99%